Capital gains taxes and asset prices the impact of tax awareness and procrastination - Eichfelder, Sebastian 1976-; Lau, Mona (Freie Univ. Berlin, FB Wirtschaftswiss., 2014)
We argue that the impact of capital gains taxation on asset pricing depends on the tax awareness of market participants. While institutional investors should be generally well-informed about tax regulations, private investors have only limited tax knowledge and resources. As a result, market reactions on tax law changes may be delayed if a considerable fraction of market participants is not fully tax-aware. In line with our argument, we find evidence that the introduction of a previously announced German flat tax on private capital gains in 2009 resulted in a temporarily strong and significant increase of trading volumes, daily returns and asset prices. Our research implies that tax law changes provide an opportunity for well-informed investors to generate arbitrage benefits. Corresponding to our estimate, the capital gains tax resulted in an increase demand for shares of 160 % as well as in an price surplus of about 7.4 % within the last two trading days 2008.
Keywords: Geschichte 2008-2009; Kapitalertragsteuer; Steuerreform; Deutschland